Strategy Planting Mark Mark Pancasila as Solution Erosion Nationalism Through Development Model Learning Education Citizenship - Azizah, Nazla (International Journal of Students Education, 2024)
Values Pancasila which originate from 5 base that is consists of from deity, humanity, unity, people’s, and justice nature universal and objective where values the meaningful that settle down and can implemented and acknowledged by all over world. Values Pancasila it works as guidelines life so that become one unity which intact for reach objective which the same. Like which we know in era globalization and modernization moment this country indonesia is faced with with challenge about solution what which must done for maintain Pancasila as the basis his country. Matter it’s called challenge for our country because it defends Pancasila no matter which easy for done by all over inhabitant country Indonesia. As a generation successor bangs akita must own flavor nationalism And patriotism Which embedded within one self we. Impact negative that produced by current globalization and modernization make generation successor nation having damaged morals. It’s really a shame and must get special attention to generation young because should as generation young they can continue the services of the hero which already fight for for build Indonesia independent. By because that’s the need grow mark which contained in pancasila on generation successor nation. This study done by writer with use method literature review which aims to discuss about “ strategy for growing mark Pancasila on character generation successor nation ” which to study from several journal and books.